Effects of poor hygiene on cytokine phenotypes in children in the tropics. Issue 1 (December 2016) - Figueiredo, C.; Amorim, L.; Vaca, M.; Chico, M.; Campos, A.; Barreto, M.; Cooper, P.
Abstract We describe immune phenotypes (innate and adaptive cytokines) according to environmental exposure using latent class analysis. A total of 310 schoolchildren living in Ecuador were assayed for spontaneous cytokine production as well as mitogen (SEB)-stimulated cytokines in whole blood cultures. We collected data on environmental exposures by questionnaire and on intestinal parasites by examination of stool samples. Latent class analysis (LCA) was used to group children according to their innate (IL-6, IL-8, IL-10 and TNF-α) and adaptive (IL-5, IL-13, IL-17, IFN-γ and IL-10) cytokine profile. We also conducted multiple-group LCA and LCA with covariates to evaluate the effect of predictors on profile membership. We identified both hyporesponsive and Th2-modified immune phenotypes produced by peripheral blood leukocytes (PBLs) that were associated with intestinal worms and birth order, providing insights into how poor hygiene mediates immunologic effects on immune-mediated diseases.